KEHUJAHAN HUKUM NEGARA SEBAGAI SUMBER HUKUM ISLAM DALAM PEMIKIRAN SAYYID MUḤAMMAD RASYÎD RIḌÂ DAN WAHBAH AZ-ZUḤAILÎ - Yaqin, Nasrullah Ainul (UIN Sunan Kalijaga Yogyakarta, 2017)
The study of the state law as the source of Islamic law in the course of usul fikih is still rarely performed by scholars of usul fikih, especially when discussing the sources of Islamic law; except what is done by Wahbah az-Zuḥailî in his usul fikih (al-Fiqh al-Islâmî), where he fully and comprehensively explains that State law can not be used as a source of Islamic law because it results from an intellectual sich. On the other hand, far beyond that, Sayyid Muḥammad Rasyîd Riḍâ has discussed in detail the state's jurisdiction as a source of Islamic law in his tafsir (al-Manâr). He accepted in absolute terms the jurisdiction of the State as a source of Islamic law from which the law contained the value of justice. Nothing else because the law of God is justice itself, as many are described in the Qur'an. According to Wahbah az-Zuḥailî the State law can not be used as a source of Islamic law because it is derived from the mere intellect, in which the scholars have agreed that pure reason can not be used as a source of Islamic law. Therefore, the law of the State can be used as a source of Islamic law if the law is based on divine revelation, either directly (Qur'an and Hadith) or not (general rules and spirit of Islamic law). In addition, although there are differences in views, there is an intersection between the two minds, which is equally acceptable to the state's jurisdiction as a source of Islamic law. Sayyid Muḥammad Rasyîd Riḍâ received the law of the State as a source of Islamic law from which the law contained justice, while Wahbah az-Zuḥailî received it from the law was based on divine revelation, whether it be directly or indirectly.Kata Kunci: Usul fikih, Hukum Negara, Sayyid Muḥammad Rasyîd Riḍâ, Wahbah az-Zuḥailî.